The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.15376/biores.15.4.9337-9350
|View full text |Cite
|
Sign up to set email alerts
|

A discrete element method model of corn stalk and its mechanical characteristic parameters

Abstract: In a simulation model of the process of corn straw crushing, its physical parameters and the model itself influence the accuracy of the numerical calculations of the discrete element method. This study attempts to improve the simulation accuracy of the crushing process and to find the optimal combination of parameters. Based on the Hertz-Mindlin with Bonding contact model, multiple particle replacement and bonding programs written using Visual Studio were imported through the application programming interface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 8 publications
1
12
0
Order By: Relevance
“…Each physical parameter of the soil model after the above treatment is highly similar to the actual situation in the region [27]. As shown in Figure 2b, the single-sphere particle model was selected as the straw model, and the Hertz-Mindlin with bonding contact model was used between the single-sphere particle models, and each physical parameter setting of the straw model was highly similar to the actual situation in the region [14]. As shown in Figure 2c, CATIA V5R21 software (Dassault Systèmes, Paris, France) was used to build the 3D solid model of the bionic straw returning machine, and its material properties were all the same as the solid prototype.…”
Section: Parameter Optimization Experiments Of Bionic Straw Returning Machine Based On Edem2018mentioning
confidence: 99%
See 1 more Smart Citation
“…Each physical parameter of the soil model after the above treatment is highly similar to the actual situation in the region [27]. As shown in Figure 2b, the single-sphere particle model was selected as the straw model, and the Hertz-Mindlin with bonding contact model was used between the single-sphere particle models, and each physical parameter setting of the straw model was highly similar to the actual situation in the region [14]. As shown in Figure 2c, CATIA V5R21 software (Dassault Systèmes, Paris, France) was used to build the 3D solid model of the bionic straw returning machine, and its material properties were all the same as the solid prototype.…”
Section: Parameter Optimization Experiments Of Bionic Straw Returning Machine Based On Edem2018mentioning
confidence: 99%
“…The planting cycle is long (6 months) in the maize growing region of northeast China [13]. Maize rootstocks are extremely thick and high in water content after maturity [14,15], resulting in extremely high power consumption [10,11] and low qualification rate of crushing length during the operation of traditional straw returning machines [12]. Related studies have shown that, compared to other maize-growing regions in China, traditional machines will improve the operational power consumption by 6-10% when operating in the maize-growing regions of northeast China [10,11,16], and the crushing length qualification rate will be reduced by 3-5% [12,17].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, scholars at home and abroad have conducted a lot of research work to obtain the discrete element simulation parameters (Syed et al 2017;Ghodki et al 2019;Qu et al 2020;Zhang et al 2020). Huan et al (2022) used bench testing and simulation testing to obtain the best combination of contact parameters for the discrete element model of king grass stem via the collision and bouncing test and slope sliding test.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the research results, a few suggestions were provided to improve the design aspects of the mill. To improve the accuracy of discrete element simulation, Zhang et al (2020) imported multiple particle replacement and bonding programs through the application programming interface (API) of a discrete element method model. A discrete element model of corn straw was established, and the grinding process was simulated.…”
Section: Introductionmentioning
confidence: 99%